FACTORS AFFECTING CARBON DIOXIDE EMISSIONS IN INDONESIA - Agus Tri Tri Basuki; Anggi Stioningrum (Jurnal Ekonomi, 2023)
Carbon dioxide emission is one result of human activities in everyday life. Carbon dioxide emissions if left unchecked will damage the environment which will have an impact in the future. This study aims to determine how much influence economic growth, foreign investment, energy consumption and population have on carbon dioxide emissions in Indonesia. This study uses secondary data for the period 1980-2021 sourced from the Indonesian Central Statistics Agency (BPS), the Investment Coordinating Board, the World Bank, Our World In data and Energy Outlook. The analysis model uses the Vector Error Correction Model (VECM). The results of the study show that economic growth, foreign investment, and energy consumption do not have a significant effect in the short term, but in the long term they have a significant effect on carbon dioxide emissions. Population does not have a significant influence on carbon dioxide emissions in Indonesia, both in the short and long term.